The influence of the OPRM1 (A118G) polymorphism on behavioral and neural correlates of aggression in healthy males. (15th September 2019) - Weidler, Carmen; Wagels, Lisa; Regenbogen, Christina; Hofhansel, Lena; Blendy, Julie A.; Clemens, Benjamin; Montag, Christian; Habel, Ute
Abstract: Current models of aggression suggest that in addition to personality traits and environmental factors, biological vulnerability associated with genetics substantially impacts aggressive behavior. In a functional imaging study, we investigated the influence of the single nucleotide polymorphism of the mu 1 subtype opioid receptor gene ( OPRM1 ), implicated in sociability, on correlates of trait and state aggression to delineate the function of these influences in aggression. A key aim was further to differentiate different aspects of aggressive reactions – namely, the reaction to provocation and the decision to punish an opponent. 59 healthy males performed a modified Taylor Aggression Paradigm during functional magnetic resonance imaging. The implementation of the paradigm allowed for individual assessments of the decision to behave aggressively, the experience of provocation and the ramification of punishment for the participant or the opponent. The influence of variation in the OPRM1 gene was measured by the functional A118G polymorphism. G allele carriers showed lower levels of general aggression and self-reported physical aggression. Additionally, these participants exhibited increased activation in dorsolateral prefrontal, orbitofrontal, anterior cingulate and insular cortices when choosing higher punishments for the opponent. The OPRM1 polymorphism did not influence aggression in reaction to social provocation. Thus, we suggest that this genetic variant affects one's trait aggressiveness rather than actual behavioral reactivity to provocation. Investigating brain regions that are specifically linked to provocation yielded activation in cortico-limbic circuits which might mediate the evaluation of provocation and the experience of anger and thus shed light on neural processes underlying the risk for aggressive behavior. This article is part of the Special Issue entitled 'Current status of the neurobiology of aggression and impulsivity'. Highlights: The A118G polymorphism influences human aggressive behavior. G allele carriers report lower physical aggression and act less aggressively. G allele carriers show increased brain activation during aggressive decision making. Reactivity to social provocation seems to be unaffected by the A118G polymorphism.